2011
DOI: 10.1093/heapro/dar046
|View full text |Cite
|
Sign up to set email alerts
|

Popular education for health promotion and community empowerment: a review of the literature

Abstract: While there is now general agreement that the most effective way to promote health and decrease health inequities is by creating more just economic, social and political conditions, there is much less agreement about concrete ways in which public health practitioners can work with communities to address inequities such as poverty, racism and powerlessness. Practical strategies are desperately needed. Popular education, also known as Freirian and empowerment education, has been used successfully to create more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(97 citation statements)
references
References 38 publications
1
89
0
6
Order By: Relevance
“…Regarding the fields of action proposed by the Ottawa Charter, the studies were centered on reorientation of the health systems and services and developing personal abilities while the remaining fields have only been poorly outlined. According to Wiggins (2011), empowerment is the key for health promotion whereas popular education is considered an effective method to increase it and, therefore, to improve health. Traditional education that offers information, leaflets and group lectures is important in order to inform patients about their disease; however, it is not enough (Holmström, Röing, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the fields of action proposed by the Ottawa Charter, the studies were centered on reorientation of the health systems and services and developing personal abilities while the remaining fields have only been poorly outlined. According to Wiggins (2011), empowerment is the key for health promotion whereas popular education is considered an effective method to increase it and, therefore, to improve health. Traditional education that offers information, leaflets and group lectures is important in order to inform patients about their disease; however, it is not enough (Holmström, Röing, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A specific recommendation was to provide connections to the methods and norms of Participatory Action Research (PAR), which emphasizes the need for reflexive practice and embodies a rich legacy of efforts to support community capacity and confront ethical issues in research (Greenwood andLevin 2006, Long et al 2015). PAR and a variety of related approaches sprang from the popular education movement and work led by Paulo Freire (1970), Orlando Fals-Borda (1987, and others, which emphasizes inclusion of groups that will be impacted by an action in the problem-solving and solution-generating dialogue (Wiggins 2012, Freire 1970. To support such approaches, café participants suggested that the association could offer training for scientists especially in humility, ethics, and cultural competency (Quigley et al 2015, Tervalon andMurrayGarcia 1998).…”
Section: Csa-associationmentioning
confidence: 99%
“…A secondary search was conducted within: (i) journals related to health promotion, participatory research and community psychology which were not registered in the databases; and (ii) the references of included studies and within the references of existing systematic and non-systematic reviews on empowerment and health promotion (14)(15)(16)(17)(18) . This procedure yielded the identification of eleven additional studies.…”
Section: Methodsmentioning
confidence: 99%